AN ANALYSIS OF THE WORD-FORMATION PROCESSES IN JARGON USED IN TICKET RESERVATION - Depersina Putirulan; Nico Harared (IKIP Siliwangi, 2024)
Following the epidemic, there has been a growing desire to travel and an acceleration of information technology development. As a result, several new words started to appear in society. Jargon is the phrase for the newly coined word. Numerous studies have examined jargon terms using a range of variations in their goals, approaches, and media sources. Previous research has shown that jargon words have been explored by many scholars across online platforms, newspapers, and social media. This research aims to discuss the type of jargon word-formation processes used in ticket reservations. This research is based on the Yule theory. This research is qualitative descriptive, which yields descriptive data. Data have been collected by listening and conversation, verbal or non-verbal, and written text between customers and other staff of Air India. The researcher identified six types of jargon in the word formation process used in ticket reservation: acronym, compounding, clipping, initials, derivation, and multiple processes.